2016
DOI: 10.1111/fwb.12728
|View full text |Cite
|
Sign up to set email alerts
|

Context dependency in biodiversity patterns of central German stream metacommunities

Abstract: Summary Context dependency is an emerging topic that is challenging our understanding of the factors shaping biodiversity in metacommunities. River networks and other dendritic systems provide unique systems for examining variation in the processes shaping biodiversity between different metacommunities. We examined biodiversity patterns in five benthic invertebrate data sets, from two catchments in central Germany, with the aim of exploring context dependency in these systems. We used variance partitioning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 73 publications
4
82
2
2
Order By: Relevance
“…Network structure and dispersal can interact with larger scale habitat variables like drying and elevation Bogan, Boersma, & Lytle, 2013;Canedo-Arguelles et al, 2015;Leigh & Datry, 2017) and that these interactions can be highly context dependent (Heino, Gr€ onroos, Soininen, et al, 2012;Tonkin, Heino, Sundermann, Haase, & J€ ahnig, 2016;Schmera et al 2017). Even on smaller spatial scales like the stream reach scale, natural complexity and habitat variability can directly affect the process of macroinvertebrate dispersal (Brooks, Wolfenden, Downes, & Lancaster, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Network structure and dispersal can interact with larger scale habitat variables like drying and elevation Bogan, Boersma, & Lytle, 2013;Canedo-Arguelles et al, 2015;Leigh & Datry, 2017) and that these interactions can be highly context dependent (Heino, Gr€ onroos, Soininen, et al, 2012;Tonkin, Heino, Sundermann, Haase, & J€ ahnig, 2016;Schmera et al 2017). Even on smaller spatial scales like the stream reach scale, natural complexity and habitat variability can directly affect the process of macroinvertebrate dispersal (Brooks, Wolfenden, Downes, & Lancaster, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, we first Hellinger-transformed province-by-species matrix (Legendre & Gallagher, 2001) and subsequently calculated the total beta diversity (BD total) (i.e. Recent applications of the LCBD approach are described by Tonkin et al (2016) the contribution of each site to total variation).…”
Section: Response Variablesmentioning
confidence: 99%
“…Other lake studies have found that biological assemblages with passive dispersal mode or large body size are more structured by spatial processes than local environmental conditions (Beisner et al 2006; De Bie et al 2012; Padial et al 2014). However, a large amount of variation is present in the findings depending on the studied biological group, study region, and spatial extent, leading to context dependency in the patterns detected (Alahuhta and Heino 2013; Tonkin et al 2016). One biological group showing context dependency has been aquatic macrophytes, many of which are distributed around the world due to efficient dispersal abilities and colonization strategies (Santamaría 2002; Chambers et al 2008).…”
Section: Introductionmentioning
confidence: 99%